THE PERCEPTIONS OF STUDENTS ON COLLABORATIVE LEARNING AND ITS EFFECT ON ENGLISH SPEAKING SKILL - Anindhiasti Ayu Kusuma Asri; Agustina Srirahayu; Pineda Prima Yoga (Universitas Duta Bangsa Surakarta, 2021)
The purpose of this study was to investigate students' perceptions of the application of Collaborative Learning in practicing English speaking skills and to investigate the extent of the effect of Collaborative Learning on students' English speaking skills. This research was conducted at Duta Bangsa University, Surakarta. Respondents in this study were lecturers of English courses who used Collaborative Learning as one of their teaching techniques and second semester students of Universitas Duta Bangsa Surakarta. The application of collaborative learning techniques to students at Duta Bangsa University Surakarta hasÂ Â provided space for students to improve their English skills. Although nsignificant, the application of this technique cannot be considered a failure.